Interlocutor accommodation on the variation of /tɾ/ in Chilean radio. (April 2017) - Flores, Tanya L.
Highlights: Sex of listener influences variant selection. Speakers and speaker pairs over the age of 50 favored variation. Conversational speech favors variation. Variant usage abides by and reinforces social norms. Abstract: This study examines linguistic and extra-linguistic factors that motivate the production of the affricated variant [tʃ] of the consonant cluster/tɾ/, as in otro 'other' produced as [o.tʃɾo], in Chilean Spanish, with a focus on the effect of speech accommodation. This study presents the results of a mixed-effects logistic regression analysis and two-population binomial tests that together expose multiple factors affecting /tɾ/ cluster variation in this speech community. Results of this study show that the sex and age of the immediate listeners influence variant selection, thus reinforcing the need for speech accommodation analyses in sociolinguistic research. This study updates the literature on Chilean /tɾ/ variation for middle and upper class speakers using a large dataset of professional public speech, suggesting that the affricated variant is also gaining linguistic prestige.